1988
DOI: 10.1007/bf00254121
|View full text |Cite
|
Sign up to set email alerts
|

Outcome prediction in critically ill patients by means of oxygen consumption index and simplified acute physiology score

Abstract: Both oxygen consumption index (VO2-index) and simplified acute physiology score (SAPS) are reported to be reliable predictors of the ultimate outcome in critically ill patients. The purpose of this study was to verify whether survivors and nonsurvivors have different VO2-indices and whether the prognostic potency of SAPS can be improved by addition of VO2-index as a supplemental physiological variable. In 50 mechanically ventilated surgical ICU patients with heterogeneous underlying diseases, SAPS was calculat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1988
1988
1990
1990

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…The observation that oxygen consumption rose with delivery appeared to reflect an oxygen debt as well as an increase in metabolic rate. Van Lanschot et al, (1988) attempted to combine data on oxygen transport variables with SAPS and reported that there was no improvement in predictive accuracy although his conclusions have been criticized (Shoemaker, 1989).…”
mentioning
confidence: 99%
“…The observation that oxygen consumption rose with delivery appeared to reflect an oxygen debt as well as an increase in metabolic rate. Van Lanschot et al, (1988) attempted to combine data on oxygen transport variables with SAPS and reported that there was no improvement in predictive accuracy although his conclusions have been criticized (Shoemaker, 1989).…”
mentioning
confidence: 99%